SARS-CoV-2 productively infects primary human immune system cells in vitro and in COVID-19 patients - Pontelli, Marjorie C; Castro, Ítalo A; Martins, Ronaldo B; La Serra, Leonardo; Veras, Flávio P; Nascimento, Daniele C; Silva, Camila M; Cardoso, Ricardo S; Rosales, Roberta; Gomes, Rogério; Lima, Thais M; Souza, Juliano P; et al. (Journal of molecular cell biology, 2022)
Abstract The severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection is associated with a hyperinflammatory state and lymphocytopenia, a hallmark that appears as both signature and prognosis of disease severity outcome. Although cytokine storm and a sustained inflammatory state are commonly associated with immune cell depletion, it is still unclear whether direct SARS-CoV-2 infection of immune cells could also play a role in this scenario by harboring viral replication. We found that monocytes, as well as both B and T lymphocytes, were susceptible to SARS-CoV-2 infection in vitro, accumulating double-stranded RNA consistent with viral RNA replication and ultimately leading to expressive T cell apoptosis. In addition, flow cytometry and immunofluorescence analysis revealed that SARS-CoV-2 was frequently detected in monocytes and B lymphocytes from coronavirus disease 2019 (COVID-19) patients. The rates of SARS-CoV-2-infected monocytes in peripheral blood mononuclear cells from COVID-19 patients increased over time from symptom onset, with SARS-CoV-2-positive monocytes, B cells, and CD4+ T lymphocytes also detected in postmortem lung tissue. These results indicated that SARS-CoV-2 infection of blood-circulating leukocytes in COVID-19 patients might have important implications for disease pathogenesis and progression, immune dysfunction, and virus spread within the host.